P304 Night shift work and breast cancer risk: a combined analysis of population-based case-control studies with complete shift-work histories using a common definition of night work. (1st September 2016) - Cordina-Duverger, Emilie; Popa, Alexandru; Guenel, Pascal; Fritschi, Lin; Glass, Deborah; Grundy, Anne; Spinelli, John; Aronson, Kristan; Rabstein, Sylvia; Harth, Volker; Pesch, Beate; Brüning, Thomas; et al.
Abstract : Shift work involving circadian disruption was classified as probably carcinogenic (group 2A) by IARC in 2007 based on sufficient evidence in experimental animals and limited evidence in humans. To date, the evidence of an association between night shift work and breast cancer risk available from epidemiological studies remains limited, mainly because of the heterogeneity of exposure assessment methods that were used in these studies. Several meta-analyses have been conducted but could not adequately harmonise exposure assessment of shift work. To overcome this limitation, we are conducting a combined analysis of the major population-based case–control studies on breast cancer using a common definition of night work to characterise exposure. We will combine individual data from population-based studies with complete job histories and detailed night work schedules conducted in France, Germany, Spain, Canada, and Australia, including approximately 5000 breast cancer cases and 5000 controls. Breast cancer risk will be investigated in relation to a common definition of night work across the studies (e.g. at least 3 hours between midnight and 5 am), using exposure duration (in years), intensity (number of nights per month), and number of consecutive nights as the main exposure variables. Specific exposure windows during lifetime will also be considered. Analyses will also be conducted after stratification on occupation (healthcare, flight attendants, etc.) to assess the effect of occupation-specific patterns of night work schedule on breast cancer risk. We will also study the association of night work with breast cancer subtypes (ER, PR and HER2 receptor status). Sensitivity analyses using varying definitions of night work schedules will be conducted. Preliminary results will be presented at the meeting. This re-analysis of epidemiological data will provide further insight on the role of night work on breast cancer based on a large epidemiological dataset with high statistical power.